Orthopaedic Trauma in the Austere Environment A Practical Guide to Care in the Humanitarian Setting - Robinson, Juan de Dios (Springer International Publishing : Imprint: Springer, 2016)
Orthopaedic trauma represents 75% of the casualties in a disaster. Many of these patients will be cared for by international volunteers. Unfortunately, good intentions are not always matched by good preparation, often resulting in further complications for patients. This book has been written by a team of international experts with extensive experience of field missions to the most precarious and austere environments in the world, such as Afghanistan, Sierra Leone, Haiti, and Syria. After reading the text, volunteers will be able to face situations that are confusing, chaotic, and distressing with a greater sense of direction and confidence. Health care workers involved in the care of the traumatized patient will find in the book answers and guidance that will help them to negotiate their way through the myriad of unfamiliar cases they will face in the field. The text is divided into sections, each addressing a theme: definition of the austere environment, how best to prepare for missions, how to deal with injuries in austere conditions, how to ensure a positive legacy, and the need for cultural, political, and legal awareness. All of the most common orthopaedic presentations encountered in the austere environment are covered. In addition to evidence-based research, cases and actual experiences from the authors' missions are included to illustrate and bring to life key points.